Wide space sowing achieved high productivity and effective nitrogen use of irrigated wheat in South Shanxi, China - Qiang Wang; Hafeez Noor; Min Sun; Aixia Ren; Yu Feng; Peng Qiao; Jingjing Zhang; Zhiqiang Gao (PeerJ, 2022)
Wheat (Triticum aestivum L.) is a staple crop worldwide, and its yield has improved since the green revolution, which was attributed to chemical nitrogen (N) fertilizer application. However, regular N application decreases N use efficiency (NUE, the ratio of grain dry matter yield to N supply from soil and fertilizer). Various practices have been implemented to maintain high crop yield and improve NUE. Nowadays, the enhanced sowing method, i.e., wide space sowing (WS), has improved the productivity of wheat crops. However, how the sowing method and N application rate affect N use and yield productivity has not been fully elucidated. Field experiments with treatments using two sowing methods (WS, and drill sowing, DS) and four N application rates (0, 180, 240, and 300 kg ha−1, represented as N0, N180, N240, and N300, respectively) were conducted from 2017 to 2019. The results showed that grain yield under WS was 13.57–16.38% higher than that under DS. The yield advantage under WS was attributed to an increased ear number. Both the higher stem and productive stem percentage accounted for the increased ear number under WS. Higher total N quantity and larger leaf area index at anthesis under WS contributed to higher dry matter production, resulting in higher grain yield. Higher dry matter production was due to pre-anthesis dry weight and post-anthesis dry weight. The wheat crop under WS had a 12.44–15.00% higher NUE than that under DS. The increased NUE under WS was attributed to higher N uptake efficiency (the ratio of total N quantity at maturity to N supply from soil and fertilizer), which was the result of greater total N quantity. The higher total N quantity under WS was due to both higher pre-anthesis N uptake and post-anthesis N uptake. Remarkably, compared to DS with 240 kg N ha−1, WS with 180 kg N ha−1 had almost equal grain yield, dry matter, and total N quantity. Therefore, wheat crops under WS could achieve both high NUE and grain yield simultaneously with only moderate N fertilizer in South Shanxi, China.